Association of chloride intracellular channel 4 and Indian hedgehog proteins with survival of patients with pancreatic ductal adenocarcinoma. Issue 6 (16th February 2017) - Zou, Qiong; Yang, Zhulin; Li, Daiqiang; Liu, Ziru; yuan, Yuan
Summary: Pancreatic cancer is the fourth most common cause of cancer‐related mortality. Novel molecular biomarkers need to be identified for personalized medicine and to improve survival. The aim of this study was to examine chloride intracellular channel 4 (CLIC4) and Indian Hedgehog (Ihh) expression in benign and malignant lesions of the pancreas and to examine the eventual association between CLIC4 and Ihh expression, with clinicopathological features and prognosis of pancreatic cancer. A retrospective study of specimens collected from January 2000 to December 2011 at the Department of Pathology of the Second and Third Xiangya Hospitals, Central South University was undertaken to explore this question. Immunohistochemistry of CLIC4 and Ihh was performed with EnVision ™ in 106 pancreatic ductal adenocarcinoma specimens, 35 paracancer samples (2 cm away from the tumour, when possible or available), 55 benign lesions and 13 normal tissue samples. CLIC4 and Ihh expression in pancreatic ductal adenocarcinoma were significantly higher than in paracancer tissue and benign lesions (CLIC4: P  = 0.009 and Ihh: P  < 0.0001; CLIC4: P  = 0.0004 and Ihh: P  = 0.0001 respectively). CLIC4 and Ihh expression was negative in normal pancreatic tissues. The expression of CLIC4 and Ihh was associated significantly with tumour grade, lymph node metastasis, tumour invasion and poor overall survival. Thus CLIC4 and Ihh could serve as biological markers for the progression, metastasis and/or invasiveness of pancreatic ductal adenocarcinoma.